Epithelioid Sarcoma: Opportunities for Biology-Driven Targeted Therapy - Noujaim, Jonathan; Thway, Khin; Bajwa, Zia; Bajwa, Ayeza; Maki, Robert G.; Jones, Robin L.; Keller, Charles (Frontiers in Oncology, 2015)
Epithelioid sarcoma is a soft tissue sarcoma of children and young adults for which the preferred treatment for localised disease is wide surgical resection. Medical management is to a great extent undefined, and therefore for patients with regional and distal metastases, the development of targeted therapies is greatly desired. In this review we will summarize clinically-relevant biomarkers (e.g., SMARCB1, CA125, dysadherin and others) with respect to targeted therapeutic opportunities. We will also examine the role of EGFR, mTOR and polykinase inhibitors (e.g., sunitinib) in the management of local and disseminated disease. Towards building a consortium of pharmaceutical, academic and non-profit collaborators, we will discuss the state of resources for investigating epithelioid sarcoma with respect to cell line resources, tissue banks, and registries so that a roadmap can be developed towards effective biology-driven therapies.